Exploring context-specific agroecological Integrated Soil Fertility Management (ISFM) strategies for enhanced sorghum productivity and livelihoods in Hwange District, Zimbabwe - Dube, Farayi; Magaisa, Alec; Dube, Thabani; Moyo, Martin (International Crops Research Institute for the Semi-Arid Tropics, 2024)
Climate change poses a significant challenge to Sub-Saharan Africa, with erratic rainfall patterns, prolonged droughts, and increased frequency of extreme weather events. These disruptions to agricultural production cycles exacerbate food shortages. Land degradation, driven by deforestation, overgrazing, and unsustainable farming practices, further diminishes soil fertility and reduces agricultural productivity. Agroecology offers a promising pathway towards more sustainable and resilient agricultural systems. ISFM, which synergistically combines organic fertilizers, mineral fertilizers, and improved germplasm, is seen as a pivotal entry point for transitioning smallholder farming systems in Africa towards agroecological production. This study aimed to assess the adoption levels of Integrated Soil Fertility Management (ISFM) practices among male and female sorghum farmers in Zimbabwe, analyze existing sorghum production systems, identify gender-based disparities in access to and utilization of ISFM technologies and inputs, and develop context-specific recommendations for enhancing sorghum productivity, ecosystem services, and livelihoods through agroecological ISFM strategies. The study was conducted in Hwange District, Zimbabwe, a semi-arid region reliant on rain-fed agriculture. Data collection involved in-depth interviews with selected farmers using a structured questionnaire. Descriptive statistics were used to summarize quantitative data. This study provides snapshot on the current state of ISFM practices among smallholder farmers in Hwange District, Zimbabwe. The study revealed a mixed picture of ISFM adoption among sorghum farmers in Zimbabwe. While encouraging trends exist, such as the high adoption of improved varieties (76.20% for females and 78.50% for males) and the widespread use of intercropping (around 50% for both genders), several challenges hinder optimal ISFM implementation. A significant proportion of farmers utilize improved varieties and apply basal and top-dressing fertilizers, indicating a degree of adoption of input-based approaches. However, the application rates of these inputs are often suboptimal. Sorghum yields have exhibited significant variability and a decline over recent seasons, highlighting the vulnerability of production systems to climate shocks, such as the 2023/24 El Niño-induced drought. Over-reliance on crop production, particularly sorghum, exposes households to significant climate-related risks and limits livelihood diversification opportunities. Significant gender disparities exist in access to key agricultural assets, limiting women's ability to adopt and implement effective ISFM practices. While the overall gender disparities in the adoption of some practices are minimal, there are notable differences in access to resources and inputs, such as land, livestock, and agricultural machinery, which can significantly impact women's ability to adopt and benefit from ISFM practices. The study observed sub-optimal utilization of several key ISFM practices, including low rates of manure and fertilizer application, limited adoption of composting and mobile kraaling, and a slight decline in the use of intercropping and residue mulching. These findings underscore the need for targeted interventions to address the identified challenges and enhance the adoption and effectiveness of ISFM practices among sorghum farmers in Zimbabwe.